EXAMINING ETHICAL REASONING AMONG MILLENNIAL SUPERVISORS IN MALAYSIA: A PRELIMINARY STUDY - Siti Salmah Abu Bakar; Nadzri Ab Ghani, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
Nowadays, millennials face unethical workplace behaviour, yet research indicates their actions are no different from older generations, suggesting millennials tend to perform wrongdoings as if they are not equipped with ethical conduct. Hence, a pilot study was carried out as a pre-test for a primary study on millennials’ ethical reasoning. The study employs cognitive moral development theory to investigate the application of ethical reasoning to millennials' ethical behaviour. Descriptive analysis and a short version of Rest’s Defining Issues Test (DIT) were applied to examine millennials' ethical reasoning level, i.e., supervisors, for their ethical behaviour. Generally, the ethical reasoning of Malaysian supervisors is in the “middle third” category following Kohlberg’s cognitive moral development stages. Implications for theory and practice of findings are discussed.